A Brief Review of Silicosis in the United States - Carson R. Thomas; Timothy R. Kelley (Environmental Health Insights)
Silicosis may be defined as the disease resulting from chronic occupational exposure to silica dust. Silica is primarily composed of quartz dust and has been classified since 2000 as a known human carcinogen by the U.S. government. Silicosis may lead to impairment of lung function resulting from fibrosis of the lungs. This may in turn lead to an increased susceptibility to the development of tuberculosis. Respirable particles are in the size range of less than one micrometer to as large as 30 micrometers. Silicosis is an untreatable, but preventable disease. This review explores the history of silicosis in the U.S. mining industry, including case studies of occupational silicosis.